Waiting for my real life personal and public battles over obesity - Harrisan, Michael; Bowie, Geoffl; Film for the Humanities & Sciences (Hamilton, NJ : Films for the Humanities and Sciences, 2009)
'This program explores the politics and personal stories behind obesity, one of America's greatest health threats.'-- Container.
Writer, Geoff Bowie.
Narrator: Michael Harrison.
DVD format.
Keywords: Weight loss; Obesity -- United States